Preharvest Foliar Spray of Calcium Chloride on Growth, Yield, Quality, and Shelf Life Extension of Different Lowland Tomato Varieties in Malaysia - Mohammad Nurun Nabi Mazumder (MDPI AG, 2021)
Tomato is a popularly consumed vegetable fruit and suffers from huge losses due to its high perishability. Calcium chloride (CaCl2∙2H2O) application has been shown to be an important method that can extend the shelf life of tomato fruits. The current study aimed to determine the effect of pre-harvest treatments of CaCl2 on the growth, yield, quality, and shelf-life performance of tomato varieties. Four tomato varieties known as MT-1, MT-3, 303, and 105 were sprayed with the CaCl2 solutions (0.0%, 1.0%, 1.5%, and 2.0%, w/v) after seven days of fruit initiation and were sprayed every week until the first harvest. Spraying with 2% of CaCl2 showed an improvement in controlling physiological disorders such as blossom end rot (BER), weight loss, declined disease incidence, and disease severity. An increase in fruit quality was also observed as the treated fruit could maintain its shelf life up to 20 days at ambient conditions. At the highest doses of CaCl2 (2%), it increased the total ascorbic acid (AA), lycopene content, total phenolic content (TPC), and antioxidant activity (DPPH) in comparison to lower doses and control tomatoes. MT-3 responded well to higher doses of CaCl2 (2%) among the four tomato varieties and performed better in growth, yield, disease, insect infestation, quality, and shelf-life performance compared to the other varieties and CaCl2 treatment combination.